Maternal immune activation evoked by polyinosinic:polycytidylic acid does not evoke microglial cell activation in the embryo - Smolders, Silke; Smolders, Sophie M. T.; Swinnen, Nina; Gärtner, Annette; Rigo, Jean-Michel; Legendre, Pascal; Brône, Bert (Frontiers in Cellular Neuroscience, 2015)
Several studies have indicated that inflammation during pregnancy increases the risk for the development of neuropsychiatric disorders in the offspring. Morphological brain abnormalities combined with deviations in the inflammatory status of the brain can be observed in patients of both autism and schizophrenia. It was shown that acute infection can induce changes in maternal cytokine levels which in turn are suggested to affect fetal brain development and increase the risk on the development of neuropsychiatric disorders in the offspring. Animal models of maternal immune activation reproduce the etiology of neurodevelopmental disorders such as schizophrenia and autism. In this study the poly (I:C) model was used to mimic viral immune activation in pregnant mice in order to assess the activation status of fetal microglia in these developmental disorders. Because microglia are the resident immune cells of the brain they were expected to be activated due to the inflammatory stimulus. Microglial cell density and activation level in the fetal cortex and hippocampus were determined. Despite the presence of a systemic inflammation in the pregnant mice, there was no significant difference in fetal microglial cell density or immunohistochemically determined activation level between the control and inflammation group. These data indicate that activation of the fetal microglial cells is not likely to be responsible for the inflammation induced deficits in the offspring in this model.